2017
DOI: 10.1200/jco.2016.67.0893
|View full text |Cite
|
Sign up to set email alerts
|

Reduced CD62L Expression on T Cells and Increased Soluble CD62L Levels Predict Molecular Response to Tyrosine Kinase Inhibitor Therapy in Early Chronic-Phase Chronic Myelogenous Leukemia

Abstract: Purpose Immunologic surveillance of minimal residual disease in chronic myelogenous leukemia (CML) may be relevant for long-term control or cure of CML. Little is known about immune-modulatory effects of nilotinib in vivo, potentially predicting response to therapy. Patients and Methods A prospective and comprehensive flow cytometry-based immunomonitoring program paralleled the ENEST1st clinical study, investigating 52 nilotinib-naïve patients with chronic-phase CML. Data were verified in independent validatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 42 publications
2
22
0
1
Order By: Relevance
“…Sopper et al (57) have reported decreased CD62L surface expression on T cells in CML patients at diagnosis. Another mechanism of impaired immune response in CML may involve aberrant PD-1/PD-L1 signaling on effector cells, and immunosuppressive Treg, which also express PD-1.…”
Section: Effector Cells Of the Immune System In CML Patients At Diagnmentioning
confidence: 99%
“…Sopper et al (57) have reported decreased CD62L surface expression on T cells in CML patients at diagnosis. Another mechanism of impaired immune response in CML may involve aberrant PD-1/PD-L1 signaling on effector cells, and immunosuppressive Treg, which also express PD-1.…”
Section: Effector Cells Of the Immune System In CML Patients At Diagnmentioning
confidence: 99%
“…peripheral blood (PB) of CML patients [7,8]. In addition, high CD62L+ T cells and low sCD62L+ have been suggested to predict optimal treatment response to nilotinib [9]. Although it is difficult to prove the direct causal relationship of the immune system and therapy response in patients, data from TKI discontinuation studies suggest that immune response is one of the important biological factors in successful treatment-free remission (TFR) [1,[10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous works have demonstrated that the transendothelial migration of lymphocytes in CLL is accompanied by a downregulation of L‐selectin on circulating B‐CLL cells and it was also demonstrated that low L‐selectin expression on these cells is a negative prognostic factor . In a recent publication , it was also found, that L‐selectin levels on T‐lymphocytes in chronic myeloid leukemia patients are associated with the success of treatment, that is, low surface L‐selectin on T‐cells and elevated soluble L‐selectin levels were found to be an unfavorable sign for tyrosine kinase inhibitor treatment.…”
Section: Discussionmentioning
confidence: 96%